Public relations cases international perspectives - DeSanto, Barbara 1950-; Moss, Danny 1954- (Routledge, 2023)
"This unique collection of contemporary international public relations (PR) case studies gives the reader in-depth insight into effective public relations practice in a range of organizational contexts. The global cases demonstrate the breadth and sophistication of the public relations function, both in public and private sector organizations. This fully updated third edition of Public Relations Cases offers fresh perspectives on the changing face of contemporary public relations and the development of PR and communication strategies. Addressing the gap in PR literature, it examines political systems, climate, media ownership and structures, as well as the social values and economic conditions which shape the role and work of PR practitioners. The book follows a four-part analytical model CDAO (Context, Decisions, Actions, and Outcomes) to successfully identify the key points of comparison between cases to uncover how and why particular events occur and, critically, identifies what key factors and actions we can learn from in future decision-making. Featuring updated cases from across industries and around the world, including South East Asia, Latin America, the UK and the US, this book is an invaluable resource for researchers, postgraduate and executive education students studying public relations, corporate communication and public affairs"--